2008
DOI: 10.1002/art.23538
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary prevalence and incidence of work disability associated with rheumatoid arthritis in the US

Abstract: Objective. To provide a contemporary estimate of the prevalence and incidence of rheumatoid arthritis (RA) work disability and examine its permanence over time. Methods. Data were collected semiannually from 5,384 subjects with rheumatologist-diagnosed RA. We examined prevalence in subgroups formed by ϳ5-year disease duration intervals using data from subjects age <64 years who were employed at disease onset. Annual incidence was examined longitudinally among subjects who supplied data in 2003, 2004, or 2005, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 9 publications
1
53
0
Order By: Relevance
“…Before the era of therapy with a biologic agent, RA resulted in significant absenteeism and therefore substantial productivity losses (11,12). The first years of disease were found to be particularly important in establishing permanent disability and high disability costs (13)(14)(15).apy with new biologic agents and treatment strategies on WP in RA patients, reporting a decrease in WP loss, but most of these studies were controlled trials over short periods and often enrolled patients with established RA (16 -23).…”
Section: Introductionmentioning
confidence: 99%
“…Before the era of therapy with a biologic agent, RA resulted in significant absenteeism and therefore substantial productivity losses (11,12). The first years of disease were found to be particularly important in establishing permanent disability and high disability costs (13)(14)(15).apy with new biologic agents and treatment strategies on WP in RA patients, reporting a decrease in WP loss, but most of these studies were controlled trials over short periods and often enrolled patients with established RA (16 -23).…”
Section: Introductionmentioning
confidence: 99%
“…US residents with arthritis who are working report that, on average, they miss 1 day of work every 2 weeks due to arthritis-related impairments (4). A number of longitudinal studies have reported a work attrition rate of 26 -33% following an initial diagnosis of rheumatoid arthritis (RA), and that 50% of individuals with RA are projected to be unable to work 10 years after the initial diagnosis (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of RA and OA patients were restricted to the determination of fibromyalgia status and the presence or absence of SSD, as described below. Detailed analyses of disability in RA has been reported previously by the NDB (17,18), as have detailed comparisons of predictor variables in RA versus fibromyalgia (19).…”
Section: Methodsmentioning
confidence: 99%